Establishing community partnerships to maintain social connection and healthcare access during an emergency declaration: virtual veterans socials - Jay A. Gorman; Jay A. Gorman; Elizabeth S. Chamberlin; Helen P. Hailes; Marsha Langer Ellison; Rachelle M. Calixte; Jessica Mack; John Smolinsky; Erin D. Reilly; Erin D. Reilly; Charles E. Drebing (Frontiers in Public Health)
This community case study reflects the transition of a community-based social intervention at a Veterans Affairs (VA) Medical Center in the northeastern United States (U.S.) from in-person to virtual gatherings during COVID-19 restrictions. Initially, the Veterans Socials program began in 2014 to address social support challenges of veterans who received care from VA, then evolved into community-based social groups delivered with and for the veteran community. These consist of veteran-led weekly meetups aimed at fostering social connection and reducing isolation. This evaluation explores the challenges and opportunities involved in shifting to a virtual platform, focusing on how community partnerships, including collaboration between private and government organizations, supported the continuity of this inclusive social support initiative. Leveraging these partnerships expanded access to health-related resources and services, while maintaining critical social networks. Findings include program-level data and three individual case studies that underscore the role of social support systems in mitigating loneliness and improving healthcare accessibility in times of crisis. This evaluation highlights how community partnerships were essential for sustaining social support, enhancing access to healthcare information, and disseminating vital information to the community during an emergency declaration.